Wild mushroom poisoning in Kumaon region of Uttarakhand: a case series - Nikhurpa, Vinita; Nikhurpa, Mamta (International Journal of Advances in Medicine, 2021)
Mushrooms have been dietary source in hilly and ethnic tribes of India. More than 5000 mushroom species are known worldwide and nearly 100 species are known to be poisonous for humans. Mushroom poisoning occurs due to unintentional and accidental ingestion of poisonous mushroom due to misidentification of poisonous variety as edible one. There has been increasingly incidence of reporting of mushroom poisoning cases nowadays. Here we are reporting case series of 4 patients admitted hailing from same village with accidental ingestion of poisonous mushrooms with clinical-laboratory profile and outcome at our institution. Mushroom Poisoning is an emerging healthcare concern nowadays. Education and mass awareness for identification of poisonous mushrooms is an important preventive measure. Early hospitalization, proper hydration, gastric decontamination, silibinin and N- acetyl cysteine therapy with hepato-renal support constitutes mainstay of treatment. Delay in treatment and complications results in poor prognosis and mortality.